Effect of specific amino acids on hepatic lipid metabolism in fructose-induced non-alcoholic fatty liver disease. Issue 1 (February 2016) - Jegatheesan, Prasanthi; Beutheu, Stéphanie; Ventura, Gabrielle; Sarfati, Gilles; Nubret, Esther; Kapel, Nathalie; Waligora-Dupriet, Anne-Judith; Bergheim, Ina; Cynober, Luc; De-Bandt, Jean-Pascal
Summary: Background & aim: Fructose diets have been shown to induce insulin resistance and to alter liver metabolism and gut barrier function, ultimately leading to non-alcoholic fatty liver disease. Citrulline, Glutamine and Arginine may improve insulin sensitivity and have beneficial effects on gut trophicity. Our aim was to evaluate their effects on liver and gut functions in a rat model of fructose-induced non-alcoholic fatty liver disease. Methods: Male Sprague–Dawley rats (n = 58) received a 4-week fructose (60%) diet or standard chow with or without Citrulline (0.15 g/d) or an isomolar amount of Arginine or Glutamine. All diets were made isonitrogenous by addition of non-essential amino acids. At week 4, nutritional and metabolic status (plasma glucose, insulin, cholesterol, triglycerides and amino acids, net intestinal absorption) was determined; steatosis (hepatic triglycerides content, histological examination) and hepatic function (plasma aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, bilirubin) were assessed; and gut barrier integrity (myeloperoxidase activity, portal endotoxemia, tight junction protein expression and localization) and intestinal and hepatic inflammation were evaluated. We also assessed diets effects on caecal microbiota. Results: In these experimental isonitrogenous fructose diet conditions, fructose led to steatosis with dyslipidemia but without altering glucose homeostasis, liver function or gut permeability. Fructose significantly decreased Bifidobacterium and Lactobacillus and tended to increase endotoxemia. Arginine and Glutamine supplements were ineffective but Citrulline supplementation prevented hypertriglyceridemia and attenuated liver fat accumulation. Conclusion: While nitrogen supply alone can attenuate fructose-induced non-alcoholic fatty liver disease, Citrulline appears to act directly on hepatic lipid metabolism by partially preventing hypertriglyceridemia and steatosis.